The Use of Code Switching in Research Proposal Seminar - Muhammad Rahmat (Universitas Syiah Kuala, 2018)
This study aimed at investigating the types of code switching made by the students of English Education Department of Teacher Training and Education Faculty of Syiah Kuala University within research proposal seminar. It also tried to find out the students’ reasons made code switching from English to Bahasa Indonesia. A descriptively qualitative study was undertaken by observing the seminar conducted by the students and interviewing them in order to attain the needed data in this study. The results of the study showed that there were three types of code switching used by English Department students namely inter-sentential switching, intra-sentential switching, and tag/emblematic switching in which inter-sentential switching was the most frequent type of code switching made by the students while doing the researcher proposal seminar. Meanwhile, delivering of understandable messages was the main reason why most students did code switching in the seminar. In conclusion, the use of code switching is a commonly phenomenon carried out by the English students in this research context because of some distinct types and reasons.